Diagnostic value of high-frequency ultrasound assessment of the lacrimal glands for primary Sjögren’s disease - Lene Terslev; Mads Ammitzbøll-Danielsen; Viktoria Fana; Nanna Surlemont Schmidt (RMD Open)
Objectives The aim of the study was to evaluate the ultrasound findings in lacrimal glands in a cohort of patients with suspected primary Sjögren’s disease (pSjD) and to assess the relationship with the diagnosis and the association with functional tests and autoantibodies.Methods Patients with suspected pSjD, evaluated by salivary gland ultrasound (SGUS) and lacrimal gland (LGUS) as part of the diagnostic set-up were included. All had unstimulated sialometry, Schirmer’s test and laboratory test done (including autoantibodies). Ultrasound examination was performed with a GE Logiq E10 (a linear 4–20 MHz transducer for SGUS and a 6–24 MHz hockey stick transducer for LGUS). The OMERACT consensus-based greyscale scoring system (0–3) for salivary glands was applied for all glands. A score of ≥2 was considered pathological.Results 30 patients were included, one was subsequently excluded due to missing data, 13 were diagnosed with pSjD according to the American College of Rheumatology/EULAR classification criteria. The sensitivity and specificity for LGUS for pSJD diagnosis were 61.5 and 87.5, respectively. The PPV and NPV values were 80.0 and 73.3, respectively—better than SGUS for the current cohort. There was no statistically significant association between LGUS and Schirmer’s test positivity (p value: 0.86), but there was a significant association between LGUS and SSA (OR: 17.4, p=0.005) as well as SSB (OR: 23.0, p=0.003).Conclusion LGUS has moderate sensitivity and high specificity for the diagnosis of pSjD. The OMERACT scoring system appears relevant for scoring pathology in the lacrimal glands using grade ≥2 as cut-off and may be a valuable supplementary tool for diagnostic evaluation in pSjD.